Impact of Shot Noise Estimation on the Secret Key Rate of a CV-QKD System - Pereira, Daniel; Silva, Nuno A.; Pinto, Armando N. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum); 2022: Anais do II Workshop de Comunicação e Computação QuânticaDO - 10.5753/wquantum.2022.223559, 2022)
In this work we present the impact of the uncertainty of the shot noise estimate on the performance of a continuous variables quantum key distribution system using a probabilistically shaped 128-APSK constellation. We demonstrate that the performance of the system is greatly degraded by the uncertainty of the shot noise estimate, with a total loss of security being possible.